Monetary Policy in an Inside-Money, Open Economy: Comment - Kapur, Basant K. (Quarterly Journal of Economics, 1981)
Journal Article Monetary Policy in an Inside-Money, Open Economy: Comment Get access Basant K. Kapur Basant K. Kapur National University of Singapore Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 96, Issue 2, May 1981, Pages 349–356, https://doi.org/10.2307/1882395 Published: 01 May 1981